Hungary after the Elections: About the Causes of the Changes in the Parliament with Regard to the Electoral System (Czech Journal of International Relations, 2024)
Zsolt Bárány:born in 1969, Hungarian foreign graduate of the University of Economics in Prague in the field of international studiesBusiness/Politics.Milan Kasimír:born 1969, graduate of the University of Economics in Prague, majoring in International Business/Politics.